Mapping conscience: network analysis into the differences in maturation of offending and non-offending adolescents - Brauw, Maurits de (International journal of offender therapy and comparative criminology, 2022)
Conscience is a diagnostically relevant concept in forensic psychiatry, but often misinterpreted as an all-or-none phenomenon. We conceptualize the conscience as a psychic function in which elements like empathy, self-conscience emotions such as shame, guilt and pride, and moral orientation work together. The differences in conscience functioning can be described in terms of developmental levels of integration. We conducted network analyses on data collected via a questionnaire survey held among 52 offending and 243 non-offending juveniles. We displayed two networks: One representing the non-offenders’ normative and one representing the offenders’ defiantly maturing conscience. As was hypothesized, in the non-offenders network, almost all elements clustered into one clinically meaningful network, indicating integration of the different elements of the normative maturing conscience. In the offenders network, the correlations between the elements were sporadic, indicating a lack of integration of the defiantly maturing conscience. The difference between the two networks was more prominent for empathy and moral orientation than for self-conscious emotions. This research supports the theory of differences in maturation of conscience instead of being an all-or-none phenomenon and calls for further research, taking a deeper look at the significance of integration of the conscience and its implications for offending behaviour.